Prevalence of active Charcot disease in the East Midlands of England. Issue 10 (2nd June 2018) - Metcalf, L.; Musgrove, M.; Bentley, J.; Berrington, R.; Bunting, D.; Mousley, M; Thompson, J.; Sprengel, M.; Turtle‐Savage, V.; Game, F.; Jeffcoate, W.
Abstract: Aims: To undertake a prospective point prevalence study of the prevalence of active Charcot neuro‐inflammatory osteoarthropathy (Charcot disease) in a circumscribed part of England and to audit the time elapsing between disease onset and first diagnosis. Methods: The prevalence of active Charcot disease of the foot during a single month was assessed by specialist foot care teams at seven secondary care services in the East Midlands region of England. Results: A total of 90 cases were identified, representing 4.3 per 10 000 of the 205 033 total diabetes population of the region. The time elapsed from first presentation to any healthcare professional until diagnosis was also assessed. While the diagnosis was suspected or confirmed in one‐third of patients within 2 weeks, it was not made for 2 months or more in 23 patients (24%). Conclusions: Non‐specialist professionals should have greater awareness of the existence of this uncommon complication of diabetes in the hope that earlier diagnosis will lead to lesser degrees of deformity. What's new?: The Charcot foot associated with diabetes is a source of considerable morbidity and cost. Nevertheless, there have been very few studies undertaken of its epidemiology. For this reason, we undertook a prospective point prevalence study in a circumscribed region of England. The prevalence study was combined with an audit of the estimated disease duration prior to expert assessment and diagnosis. Although never formally quantified, it is generally believed that diagnosis of Charcot foot disease is often delayed and this delay may worsen long‐term outcome. The prevalence of known active disease during a single month in England was 4.3 per 10 000 people with diabetes. The diagnosis was delayed for >2 months in nearly one‐quarter of cases.